Changing Demographics, Temporal Trends in Waitlist, and Posttransplant Outcomes After Heart Transplantation in the United States: Analysis of the UNOS Database 1991–2019. (25th October 2021) - Akintoye, Emmanuel; Alvarez, Paulino; Shin, Doosup; Egbe, Alexander; Panos, Anthony; Sellke, Frank; Briasoulis, Alexandros
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: We sought to investigate temporal trends in patient characteristics, waitlist, and posttransplant outcomes after heart transplantation in the United States. Methods: Using data from the United Network of Organ Sharing, we identified adults listed for heart transplantation between 1991 and 2019. Patients were divided into 4 eras based on the 3 time points in which changes were made to the patient selection/allocation policy (Era 1=January 1991–January 1999; Era 2=January 1999–July 2006; Era 3=July 2006–October 2018; and Era 4=October 2018–March 2020), and patient characteristics, waitlist, and posttransplant outcomes were evaluated for each era. Results: Between 1991 and 2019, 95 179 patients were added to the heart transplantation waitlist. Compared with Era 1, patients listed in Era 4 were older (mean age: 50 versus 52 years) and with higher risk comorbidities (eg, 10% versus 28.8% diabetes, 23.3% versus 35.6% obese). Over the study period, 22 738 patients died or were permanently delisted for deterioration on the waitlist while 61 687 were transplanted. Compared with the preceding era, there was significant decrease in death or deterioration in the last 2 eras (sub-hazard ratio, 0.67 [95% CI, 0.65–0.70] for Era 3 versus Era 2 and sub-hazard ratio, 0.65 [95% CI, 0.58–0.73] for Era 4 versus 3). Across the years, 27.1% to 40.5% of those on the waitlist were transplanted. Among those transplanted, there was increase in the rates of in-hospital stroke (2.8% in Era 1 to 3.7% in Era 4), renal failure requiring dialysis (7.2%–17.1%), and length-of-stay (14–17days), P <0.001. However, this did not negatively impact short-term survival when compared with the preceding era (1-year graft survival from Era 1 to Era 4=84.1%, 86.4%, 90.4%, and 89.7%, respectively). Conclusions: There have been significant changes in the characteristics of patients listed for heart transplantation. Although transplant volume has increased, the wide supply-demand gap persisted. The last two changes in the allocation policy achieved their primary objective of reducing waitlist mortality.